2022
DOI: 10.3390/universe8020109
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Tension between the T2K and NOνA Appearance Data and Hints to New Physics

Abstract: In this article, we review the status of the tension between the long-baseline accelerator neutrino experiments T2K and NOνA. The tension arises mostly due to the mismatch in the apappearance data of the two experiments. We explain how this tension arises based on νμ→νe and ν¯μ→ν¯e oscillation probabilities. We define the reference point of vacuum oscillation, maximal θ23 and δCP and compute the νe/ν¯e appearance events for each experiment. We then study the effects of deviating the unknown parameters from the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 156 publications
0
6
0
Order By: Relevance
“…In contrast to the breaking pattern mentioned in Eqs. (15,16), if S 4 is considered to be broken spontaneously into Z 3 = {1, T, T 2 } (for the charged lepton sector) Z 2 = {1, SU } (for the neutrino sector)…”
Section: A General Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the breaking pattern mentioned in Eqs. (15,16), if S 4 is considered to be broken spontaneously into Z 3 = {1, T, T 2 } (for the charged lepton sector) Z 2 = {1, SU } (for the neutrino sector)…”
Section: A General Frameworkmentioning
confidence: 99%
“…This implies values of the CP-violating phase in the vicinity of δ CP = π/2, disfavored by 3σ for IH, and values around δ CP = 3π/2 in NH, disfavored at 2σ for IH. For a recent review, see [15]. Let us note that the T2K, Super-Kamiokande and the NOνA collaborations are working towards joint analyses.…”
mentioning
confidence: 99%
“…Currently, while some tension between NOνA and T2K results exist regarding the Dirac CP phase for a normal neutrino-mass ordering, maximal CP violation seems to be preferred for an inverted spectrum (for a recent review see ref. [6]). In the next decades, long-baseline neutrino experiments like DUNE [7] and Hyper-Kamiokande [8] will provide much more information on leptonic CP violation (LCPV) [9].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, two independent groups have shown in their studies that presence of eµ and eτ can resolve the current NOvA and T2K tension in the measurement of CP violating phase δ CP [34,35]. In [36], it has been shown that this tension arises primarily from the ν e appearance data, while a review on the possible role of new physics leading to this tension has been discussed in [37].…”
Section: Introductionmentioning
confidence: 99%